Show Summary Details
More options …

# Open Mathematics

### formerly Central European Journal of Mathematics

Editor-in-Chief: Gianazza, Ugo / Vespri, Vincenzo

IMPACT FACTOR 2017: 0.831
5-year IMPACT FACTOR: 0.836

CiteScore 2018: 0.90

SCImago Journal Rank (SJR) 2018: 0.323
Source Normalized Impact per Paper (SNIP) 2018: 0.821

Mathematical Citation Quotient (MCQ) 2017: 0.32

ICV 2017: 161.82

Open Access
Online
ISSN
2391-5455
See all formats and pricing
More options …
Volume 16, Issue 1

# On the power sum problem of Lucas polynomials and its divisible property

Wang Xiao
Published Online: 2018-06-22 | DOI: https://doi.org/10.1515/math-2018-0063

## Abstract

The main purpose of this paper is to use the mathematical induction and the properties of Lucas polynomials to study the power sum problem of Lucas polynomials. In the end, we obtain an interesting divisible property.

MSC 2010: 11B39

## 1 Introduction

For any integer n ≥ 0, the famous Fibonacci polynomials {Fn(x)} and Lucas polynomials {Ln(x)} are defined by F0(x) = 0, F1(x) = 1, L0(x) = 2, L1(x) = x and Fn+2(x) = xFn+1(x) + Fn(x), Ln+2(x) = xLn+1(x) + Ln(x). The general terms of Fn(x) and Ln(x) are given by

$Fn+1(x)=∑k=0[n2](n−kk)xn−2k$

and

$Ln(x)=∑k=0[n2]nn−k(n−kk)xn−2k,$(1)

where $\begin{array}{}\left(\genfrac{}{}{0}{}{m}{n}\right)=\frac{m!}{n!\left(m-n\right)!},\end{array}$ and [x] denotes the greatest integer ≤ x.

It is easy to prove the identities

$Fn(x)=1x2+4[(x+x2+42)n−(x−x2+42)n]$

and

$Ln(x)=(x+x2+42)n+(x−x2+42)n.$(2)

If we take x = 1, then {Fn(x)} becomes Fibonacci sequences {Fn(1)}, and {Ln(x)} becomes Lucas sequences {Ln(1)}.

Since these sequences and polynomials have very important positions in the theory and application of mathematics, many scholars have studied their various properties, and obtained a series of important results, some of which can be found in references [1, 2, 3, 4, 5], and some other related papers can also be found in [6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. For example, in a private communication with Curtis Cooper, R. S. Melham suggested that it would be interesting to discover an explicit expansion for

$L1L2⋯L2m+1∑k=1nF2k2m+1$

as a polynomial in F2n+1. Wiemann and Cooper [1] reported some conjectures of Melham related to the sum $\begin{array}{}\sum _{k=1}^{n}{F}_{2k}^{2m+1}.\end{array}$ Kiyota Ozeki [2] proved that

$∑k=1nF2k2m+1=15m∑j=0m(−1)jL2m+1−2j(j2m+1)(F(2m+1−2j)(2n+1)−F2m+1−2j).$

Helmut Prodinger [3] studied the more general summation $\begin{array}{}\sum _{k=0}^{n}{F}_{2k+\delta }^{2m+1+ϵ},\end{array}$ where δ, ϵ ∈ {0, 1}, and obtained many interesting identities.

For the sum of powers of Lucas numbers, Helmut Prodinger [3] also obtained some similar conclusions.

R. S. Melham [4] also proposed the following two conjectures:

#### Conjecture A

Let m be a positive integer. Then the sum

$L1L3L5⋯L2m+1∑k=1nF2k2m+1$

can be expressed as (F2n+1 − 1)2 P2m−1(F2n+1), where P2m−1(x) is a polynomial of degree 2m − 1 with integer coefficients.

#### Conjecture B

Let m ≥ 0 be an integer. Then the sum

$L1L3L5⋯L2m+1∑k=1nL2k2m+1$

can be expressed as (L2n+1 − 1) Q2m(L2n+1), where Q2m(x) is a polynomial of degree 2m with integer coefficients.

Wang Tingting and Zhang Wenpeng [5] studied these problems, and proved several conclusions for $\begin{array}{}\sum _{k=1}^{h}{F}_{k}^{n}\left(x\right)\phantom{\rule{thinmathspace}{0ex}}\phantom{\rule{thinmathspace}{0ex}}\text{and}\phantom{\rule{thinmathspace}{0ex}}\phantom{\rule{thinmathspace}{0ex}}\sum _{k=1}^{h}{L}_{k}^{n}\left(x\right),\end{array}$ where h and n are any positive integers.

As some applications of Theorem 2 in reference [5], they deduced the following:

#### Corollary A

Let h ≥ 1 and n ≥ 0 be two integers. Then the sum

$L1(x)L3(x)L5(x)⋯L2n+1(x)∑m=1hL2m2n+1(x)$

can be expressed as (L2h+1(x) − x) Q2n(x, L2h+1(x)), where Q2n(x, y) is a polynomial in two variables x and y with integer coefficients and degree 2n of y.

#### Corollary B

Let h ≥ 1 and n ≥ 0 be two integers. Then the sum

$L1(x)L3(x)L5(x)⋯L2n+1(x)∑m=1hF2m2n+1(x)$

can be expressed as (F2h+1(x) − 1) H2n(x, F2h+1(x)), where H2n(x, y) is a polynomial in two variables x and y with integer coefficients and degree 2n of y.

Therefore, Wang Tingting and Zhang Wenpeng [5] solved Conjecture B completely. They also obtained some substantial progress for Conjecture A.

It is easy to see that in the above Conjecture A and Conjecture B, the subscripts of Fn and Ln in sums $\begin{array}{}\sum _{k=1}^{n}{F}_{2k}^{2m+1}\phantom{\rule{thinmathspace}{0ex}}\phantom{\rule{thinmathspace}{0ex}}\text{and}\phantom{\rule{thinmathspace}{0ex}}\phantom{\rule{thinmathspace}{0ex}}\sum _{k=1}^{n}{L}_{2k}^{2m+1}\end{array}$ are even numbers. Inspired by the above researches, we naturally ask that for any positive integers n and h with h ≥ 2, whether there exists a polynomial U(x) with degree > 1 such that the congruence

$L1(x)L3(x)⋯L2n+1(x)∑m=0h−1L2m+12n+1(x)≡0modU(x).$(3)

If so, what would U(x) look like? How is it different from the form in Conjecture A and Conjecture B ? Obviously, it is hard to guess the exact form of U(x) from (d) of Theorem 1 in reference [5]. Maybe that is why there is no such formal conjecture in [4].

In this paper, we shall use the mathematical induction and the properties of Lucas polynomials to study this problem, and give an exact polynomial U(x) in (3). The result is detailed in the following theorems.

#### Theorem A

For any positive integers n and h with h ≥ 2, we have

$L1(x)L3(x)⋯L2n+1(x)∑m=0h−1L2m+12n+1(x)≡0modx⋅(L2h(x)−2).$

#### Theorem B

For any positive integers n and h with h ≥ 2, we have

$L1(x)L3(x)⋯L2n+1(x)∑m=0h−1F2m+12n+1(x)≡0modx⋅F2h(x).$

Taking x = 1, from Theorem 1 and Theorem 2 we may immediately deduce the following two corollaries:

#### Corollary A

For any positive integers n and h with h ≥ 2, we have

$L1L3⋯L2n+1∑m=0h−1L2m+12n+1≡0mod(L2h−2).$

#### Corollary B

For any positive integers n and h with h ≥ 2, we have

$L1L3⋯L2n+1∑m=0h−1F2m+12n+1≡0modF2h.$

## 2 Two Lemmas

#### Lemma A

For any non-negative integer n and k, we have the identity

$Ln(L2k+1(x))=Ln(2k+1)(x).$

#### Proof

Let $\begin{array}{}\alpha =\frac{x+\sqrt{{x}^{2}+4}}{2},\beta =\frac{x-\sqrt{{x}^{2}+4}}{2},\end{array}$ and replace x by L2k+1(x) in (2). Since we have α2k+1β2k+1 = −1,

$L2k+1(x)+L2k+12(x)+4=α2k+1+β2k+1+(α2k+1+β2k+1)2+4=α2k+1+β2k+1+α2(2k+1)+β2(2k+1)−2+4=α2k+1+β2k+1+(α2k+1−β2k+1)2=2α2k+1$

and

$L2k+1(x)−L2k+12(x)+4=α2k+1+β2k+1−(α2k+1+β2k+1)2+4=α2k+1+β2k+1−(α2k+1−β2k+1)2=2β2k+1,$

from (2) we have the identity

$Ln(L2k+1(x))=(L2k+1+L2k+12+42)n+(L2k+1−L2k+12+42)n=αn(2k+1)+βn(2k+1)=Ln(2k+1)(x).$

This completes the proof of Lemma 1. □

#### Lemma B

For any positive integers n and h, we have the congruence

$L1(x)(L2h(2n+1)(x)−2)−(2n+1)L2n+1(x)(L2h(x)−2)≡0modx(L2h(x)−2).$

#### Proof

From (1) we know that xL2n+1(x). Because that L1(x) = x, so in order to prove Lemma 2, we only need to prove the congruence

$L2h(2n+1)(x)−2≡0mod(L2h(x)−2).$(4)

Next we prove (4) by complete induction. It is clear that (4) is true for n = 0. If n = 1, then apply the identity

$L2h3(x)=(α2h+β2h)3=L6h(x)+3L2h(x),$

we have

$L6h(x)−2=L2h3(x)−3L2h(x)−2=(L2h(x)−2)(L2h(x)+1)2≡0mod(L2h(x)−2).$

That is to say, the congruence (4) is true for n = 1.

Suppose that the congruence (4) is true for all integers 0 ≤ ns. That is,

$L2h(2n+1)(x)−2≡0mod(L2h(x)−2)$(5)

holds for all integers 0 ≤ ns.

Then for positive integer n = s + 1, we have the identities

$L4h(x)=L2h2(x)−2≡2mod(L2h(x)−2)$

and

$L4h(x)L2h(2s+1)(x)=L2h(2s+3)(x)+L2h(2s−1)(x),$

from (5) we can deduce the congruence equations as follows

$L2h(2s+3)(x)−2=L4h(x)L2h(2s+1)(x)−L2h(2s−1)(x)−2≡2L2h(2s+1)(x)−L2h(2s−1)(x)−2≡2(L2h(2s+1)(x)−2)−(L2h(2s−1)(x)−2)≡0mod(L2h(x)−2).$

That is to say, the congruence (4) is true for n = s + 1.

Now Lemma 2 follows from (4) and completes the induction. □

## 3 Proofs of the theorems

In this section, we shall use mathematical induction to complete the proofs of our theorems. Here we only prove Theorem 1. Similarly, we can also deduce Theorem 2 and thus we omit its proving process here. After replacing x by L2m+1(x) in (1), we obtain the following expression with Lemma 1

$L(2n+1)(2m+1)(x)=L2n+1(L2m+1(x))=∑k=0n2n+12n+1−k(2n+1−kk)L2m+12n+1−2k(x)$

or

$L(2n+1)(2m+1)(x)−(2n+1)L2m+1(x)=∑k=0n−12n+12n+1−k(2n+1−kk)L2m+12n+1−2k(x).$(6)

For any positive integer h ≥ 2, we first introduce that the identities

$∑m=0h−1L(2n+1)(2m+1)(x)=∑m=0h−1(α(2n+1)(2m+1)+β(2n+1)(2m+1))=α2n+1⋅α2h(2n+1)−1α2(2n+1)−1+β2n+1⋅β2h(2n+1)−1β2(2n+1)−1=α2h(2n+1)−1α2n+1+β2n+1+β2h(2n+1)−1β2n+1+α2n+1=L2h(2n+1)(x)−2L2n+1(x),$(7)

$∑m=0h−1L2m+1(x)=∑m=0h−1(α2m+1+β2m+1)=L2h(x)−2L1(x).$(8)

Then, combining (6), (7) and (8) we have

$∑m=0h−1[L(2n+1)(2m+1)(x)−(2n+1)L2m+1(x)]=L2h(2n+1)(x)−2L2n+1(x)−(2n+1)⋅L2h(x)−2L1(x)=∑k=0n−12n+12n+1−k(2n+1−kk)∑m=0h−1L2m+12n+1−2k(x).$(9)

Now we apply (9) and mathematical induction to prove the congruence

$L1(x)L3(x)⋯L2n+1(x)∑m=0h−1L2m+12n+1(x)≡0modx(L2h(x)−2).$(10)

If n = 1, then from (9) we have

$L1(x)L3(x)[L6h(x)−2L3(x)−3⋅L2h(x)−2L1(x)]=L1(x)L3(x)∑m=0h−1L2m+13(x).$(11)

From Lemma 2 we know that

$L1(x)L3(x)[L6h(x)−2L3(x)−3⋅L2h(x)−2L1(x)]≡0modx(L2h(x)−2).$(12)

Combining (11) and (12) we know that the congruence (10) is true for n = 1.

Suppose that (10) is true for all 1 ≤ ns. That is,

$L1(x)L3(x)⋯L2n+1(x)∑m=0h−1L2m+12n+1(x)≡0modx(L2h(x)−2)$(13)

holds for all 1 ≤ ns.

Then for n = s + 1, from (9) we have

$L2h(2s+3)(x)−2L2s+3(x)−(2s+3)⋅L2h(x)−2L1(x)=∑k=0s2s+32s+3−k(2s+3−kk)∑m=0h−1L2m+12s+3−2k(x)=∑m=0h−1L2m+12s+3(x)+∑k=1s2s+32s+3−k(2s+3−kk)∑m=0h−1L2m+12s+3−2k(x).$(14)

Applying Lemma 2 we have the congruence

$L1(x)L3(x)⋯L2s+3(x)[L2h(2s+3)(x)−2L2s+3(x)−(2s+3)⋅L2h(x)−2L1(x)]≡0modx(L2h(x)−2).$(15)

If 1 ≤ ks, then 3 ≤ 2s + 3 − 2k ≤ 2s + 1. From the inductive assumption (13) we have

$L1(x)L3(x)⋯L2s+1(x)L2s+3(x)∑k=1s2s+32s+3−k(2s+3−kk)∑m=0h−1L2m+12s+3−2k(x)≡0modx(L2h(x)−2).$(16)

Combining (14), (15) and (16) we may immediately deduce the congruence

$L1(x)L3(x)⋯L2s+1(x)L2s+3(x)∑m=0h−1L2m+12s+3(x)≡0modx(L2h(x)−2).$

This completes the proof of our theorem by mathematical induction.

## Acknowledgement

This work is supported by the N. S. F. (Grant No. 11771351) of P. R. China. The author would like to thank the referees for their very helpful and detailed comments, which have significantly improved the presentation of this paper.

## References

• [1]

Wiemann, M, Cooper C: Divisibility of an F-L Type Convolution, Applications of Fibonacci Numbers, Vol. 9, Kluwer Acad. Publ., Dordrecht, 2004, 267-287 Google Scholar

• [2]

Kiyota Ozeki, On Melham’s sum, The Fibonacci Quarterly, 2008/2009, 46/47, 107–110 Google Scholar

• [3]

Helmut Prodinger, On a sum of Melham and its variants, The Fibonacci Quarterly, 2008/2009, 46/47, 207–215 Google Scholar

• [4]

Melham, R. S: Some conjectures concerning sums of odd powers of Fibonacci and Lucas numbers, The Fibonacci Quarterly, 2008/2009, 46/47, 312-315 Google Scholar

• [5]

Wang, T, Zhang, W: Some identities involving Fibonacci. Lucas polynomials and their applications Bull. Math. Soc. Sci. Math. Roumanie, 2012, 55, 95–103 Google Scholar

• [6]

Li, X: Some identities involving Chebyshev polynomials. Mathematical Problems in Engineering, 2015, 2015, Article ID 950695

• [7]

Ma, Y, Lv, X: Several identities involving the reciprocal sums of Chebyshev polynomials. Mathematical Problems in Engineering, 2017, 2017, Article ID 4194579 Google Scholar

• [8]

Yi, Y, Zhang, W: Some identities involving the Fibonacci polynomials, The Fibonacci Quarterly, 2002, 40, 314–318 Google Scholar

• [9]

Ma, R, Zhang, W: Several identities involving the Fibonacci numbers and Lucas numbers, The Fibonacci Quarterly, 2007, 45, 164–170 Google Scholar

• [10]

Kim, D. S, Kim, T, Lee, S: Some identities for Bernoulli polynomials involving Chebyshev polynomials. J. Comput. Anal. Appl., 2014, 16, 172–180 Google Scholar

• [11]

Kim, D. S, Dolgy, D. V, Kim, T, Rim, S. H: Identities involving Bernoulli and Euler polynomials arising from Chebyshev polynomials. Proc. Jangjeon Math. Soc., 2012, 15, 361–370 Google Scholar

• [12]

Kim, T, Kim, D. S, Seo, J. J, Dolgy, D. V: Some identities of Chebyshev polynomials arising from non-linear differential equations. J. Comput. Anal. Appl., 2017, 23, 820–832 Google Scholar

• [13]

He, Y: Some new results on products of Apostol-Bernoulli and Apostol-Euler polynomials, J. Math. Anal. Appl., 2015, 431, 34–46

• [14]

He, Y, Wang, C. P: New symmetric identities involving the Eulerian polynomials, J. Comput. Anal. Appl., 2014, 17, 498–504 Google Scholar

• [15]

He, Y, Kim, D. S: General convolution identities for Apostol-Bernoulli, Euler and Genocchi polynomials, J. Nonlinear Sci. Appl., 2016, 9, 4780–4797

• [16]

Chen, L, Zhang, W: Chebyshev polynomials and their some interesting applications, Advances in Difference Equations, 2017, 2017: 303

Accepted: 2018-05-15

Published Online: 2018-06-22

Competing interests: The author declare that they have no competing interests.

Citation Information: Open Mathematics, Volume 16, Issue 1, Pages 698–703, ISSN (Online) 2391-5455,

Export Citation